Ultrasonic spot welding of Al–Cu dissimilar metals: a study on parametric influence and thermo-mechanical simulation. (3rd April 2018) - Satpathy, Mantra Prasad; Mohapatra, Kasinath Das; Sahoo, Susanta Kumar
Abstract: Ultrasonic welding is becoming an essential technique for joining of thin and dissimilar materials in battery electric vehicle manufacturing because of consumption of less power, unmatched weld quality, high production rate, excellent efficiency, etc. The process control parameters in welding play a vital role in getting a good quality weld. In this study, AA1100 aluminum and UNS C10100 copper are utilized for experimentation by controlling three input parameters such as weld pressure, weld time, and vibration amplitude. The effects of these control parameters on the responses like tensile shear and T-peel failure loads of joints with microstructures are revealed. Furthermore, a three-dimensional thermo-mechanical finite element (FE) model with the relevant welding mechanics is proposed for this dissimilar material combination to predict the temperature distribution in its interface, sonotrode, and anvil. The simulation results are validated by comparing the experimental temperature values, and they are showing good agreement with each other. It provides a significant insight of thermal softening phenomenon in ultrasonic welding process and demonstrates the relationship between physical attributes and the interface temperature.